2019
DOI: 10.1093/jole/lzz002
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Hierarchical Structure Evolves through Cultural Transmission: An Experimental Study

Abstract: Compositional hierarchical structure is a prerequisite for productive languages; it allows language learners to express and understand an infinity of meanings from finite sources (i.e., a lexicon and a grammar). Understanding how such structure evolved is central to evolutionary linguistics. Previous work combining artificial language learning and iterated learning techniques has shown how basic compositional structure can evolve from the trade-off between learnability and expressivity pressures at play in lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…However, these results are at odds with the prior research into iterated learning, which has repeatedly shown that learners have a bias for simplicity-not informativenessand that iterated learning therefore gives rise to simple, degenerate, uninformative languages. Informative languages only emerge in the presence of a shared communicative task (e.g., Carr et al, 2017;Kirby et al, 2015;Motamedi et al, 2019;Raviv et al, 2018;Saldana et al, 2019;Winters et al, 2018) or an artificial analog of such a task (Beckner et al, 2017;Kirby et al, 2008), neither of which was present in the two studies described by Carstensen et al (2015). One reason why learners might be biased toward simplicity is that, when learners are faced with understanding the world, the best strategy-given that they have no expectations about how the world is structured-is to apply Occam's razor; all things being equal, simpler hypotheses should be preferred over more complex ones (Li & Vitányi, 2008;Rissanen, 1978;Solomonoff, 1964).…”
Section: )mentioning
confidence: 97%
“…However, these results are at odds with the prior research into iterated learning, which has repeatedly shown that learners have a bias for simplicity-not informativenessand that iterated learning therefore gives rise to simple, degenerate, uninformative languages. Informative languages only emerge in the presence of a shared communicative task (e.g., Carr et al, 2017;Kirby et al, 2015;Motamedi et al, 2019;Raviv et al, 2018;Saldana et al, 2019;Winters et al, 2018) or an artificial analog of such a task (Beckner et al, 2017;Kirby et al, 2008), neither of which was present in the two studies described by Carstensen et al (2015). One reason why learners might be biased toward simplicity is that, when learners are faced with understanding the world, the best strategy-given that they have no expectations about how the world is structured-is to apply Occam's razor; all things being equal, simpler hypotheses should be preferred over more complex ones (Li & Vitányi, 2008;Rissanen, 1978;Solomonoff, 1964).…”
Section: )mentioning
confidence: 97%
“…(2017) or Saldana et al. (2019), much larger sets of signals were presented three times each. Again, methodological feasibility seems to determine the overall amount of training, but these different training regimens make it difficult to disentangle the effects of presentation frequency from effects of structural complexity.…”
Section: Combinatorial and Compositional Structurementioning
confidence: 99%
“…Whereas some researchers insist that symbol-trained apes have basically no understanding of ordering principles in communicative utterances at all (e.g. Terrace et al, 1979;Anderson, 2006), other researchers have presented evidence that apes such as Kanzi at least possess some kind of ordering structure in comprehension and production and at least minimal grammatical competence, possibly even some kind of semantic ordering principles (Rumbaugh et al, 1993;Hurford, 2012;Hurford, 2012;Lyn, 2012). There also has been keen interest in studying artificial grammar learning in a wide range of animals, especially birds and primates (see, e.g., ten Cate, 2017; ten Cate & Petkov, 2019 for reviews).…”
Section: Artificial Communication Systemsmentioning
confidence: 99%